2006
DOI: 10.1002/app.25019
|View full text |Cite
|
Sign up to set email alerts
|

Improved pharmacokinetics and stability properties of catalase by chemical glycosidation with end‐group activated dextran

Abstract: Catalase was chemically modified with a monoactivated dextran derivative having a carboxylate group at its reducing end residue. The modified enzyme retained 77% of its initial specific activity and was 3-fold more resistant to tryptic degradation. The plasma half-life time was increased to 7.3-fold after glycosidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Although PEGylation remains the most widely applied strategy for formulation biologics for IV administration, alternative conjugation techniques to PEGylation have been explored to prolong the delivery of biotherapeutics given by the IV route. Villalonga and co-workers have reported the preparation of dextran-catalase conjugates by using a 5 kDa dextran coupled to glutamic and aspartic acid residues on the enzyme, and with dextran activated with an ε-aminocaproic acid spacer [ 176 ]. A 20-fold (from 0.8 to 16 h) and 7-fold prolongation of half-life (from 0.7 to 5.1 h) were observed, respectively, with corresponding decrease in clearance and increase in total drug exposure [ 176 , 177 ].…”
Section: Polypeptide Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Although PEGylation remains the most widely applied strategy for formulation biologics for IV administration, alternative conjugation techniques to PEGylation have been explored to prolong the delivery of biotherapeutics given by the IV route. Villalonga and co-workers have reported the preparation of dextran-catalase conjugates by using a 5 kDa dextran coupled to glutamic and aspartic acid residues on the enzyme, and with dextran activated with an ε-aminocaproic acid spacer [ 176 ]. A 20-fold (from 0.8 to 16 h) and 7-fold prolongation of half-life (from 0.7 to 5.1 h) were observed, respectively, with corresponding decrease in clearance and increase in total drug exposure [ 176 , 177 ].…”
Section: Polypeptide Deliverymentioning
confidence: 99%
“…Villalonga and co-workers have reported the preparation of dextran-catalase conjugates by using a 5 kDa dextran coupled to glutamic and aspartic acid residues on the enzyme, and with dextran activated with an ε-aminocaproic acid spacer [ 176 ]. A 20-fold (from 0.8 to 16 h) and 7-fold prolongation of half-life (from 0.7 to 5.1 h) were observed, respectively, with corresponding decrease in clearance and increase in total drug exposure [ 176 , 177 ]. A HESylated analogue of anakinra, a recombinant human IL-1 receptor antagonist approved for the treatment of rheumatoid arthritis, has been reported [ 178 ].…”
Section: Polypeptide Deliverymentioning
confidence: 99%
“…Gel filtration studies of the fluorescein–dextran conjugates demonstrated a linear relationship between dextran size and column retention time, with larger dextrans displaying shorter retention times . In addition, conjugation of dextran has been shown to decrease in vitro enzymatic degradation of catalase and to reduce the immunogenicity of xenogeneic antibodies …”
Section: Carbohydrate Polymersmentioning
confidence: 99%
“…Dextran conjugation via a spacer has been extensively explored for small molecules, but has also been applied to peptides and enzymes . Introduction of spacers such as ϵ‐aminocaproic acid at the reducing end has enabled site‐specific conjugation of dextran to the N‐terminus of catalase subunits (Figure B) . Lastly, dextran conjugation to proteins has also been obtained by an enzymatic approach using microbial transglutaminase to attach dextran with hexylenediamine at the reducing end to surface Gln residues of catalase …”
Section: Carbohydrate Polymersmentioning
confidence: 99%
See 1 more Smart Citation